2005
DOI: 10.1016/j.seizure.2004.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Seizure-related factors and non-verbal intelligence in children with epilepsy

Abstract: In childhood epilepsy various seizure-related factors, but not SES factors, were associated with the presence or absence of SNVP. Such deficits may be especially common in children with remote symptomatic epilepsy aetiology and in complex and therapy resistant epilepsies. Low frequencies of SNVP may be found in children with idiopathic and LR cryptogenic epilepsy syndromes, simple partial or absence seizures and a late epilepsy debut. Our study contributes to an overall picture of cognitive function and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 31 publications
1
58
4
Order By: Relevance
“…The relationship between early-onset seizures and poor cognitive outcome has previously been noted in a number of population-based studies. 11,14,15 The use of polytherapy and negative cognitive outcome has also been noted 14 and probably reflects a need to try to treat drugresistant seizures. The association with ID and "predominantly generalized" seizures suggests that seizures affecting the whole of the brain may be more deleterious compared with focal seizures, which may be associated with more selective cognitive impairments, 16 and poorer global cognitive outcome has been associated with presence of generalized seizures.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between early-onset seizures and poor cognitive outcome has previously been noted in a number of population-based studies. 11,14,15 The use of polytherapy and negative cognitive outcome has also been noted 14 and probably reflects a need to try to treat drugresistant seizures. The association with ID and "predominantly generalized" seizures suggests that seizures affecting the whole of the brain may be more deleterious compared with focal seizures, which may be associated with more selective cognitive impairments, 16 and poorer global cognitive outcome has been associated with presence of generalized seizures.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this view, intellectual outcome is particularly poor if seizures begin prior to the age of five [5,[13][14][15][16][17], with the poorest outcomes associated with seizure onset in the first year of life [11,18]. The effect of age at onset persists once factors such as seizure control [14,19], number of antiepileptic drugs (AEDs) [19], etiology [20], duration of epilepsy [14,19,21], and extent of pathology are controlled [22], implying that developmental processes have an independent effect on cognitive outcome.…”
Section: Introductionmentioning
confidence: 94%
“…Some recent studies have explored the relationship between age at seizure onset and specific cognitive functions across childhood. These studies have yielded mixed results, with age at seizure onset found to predict motor function [23], attention [6], language [8], nonverbal reasoning [16], memory [24], and executive functions [25,26]. However, several studies have reported the absence of such effects across these cognitive domains [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The study population and control group have been described previously (Waaler et al 2000, Høie et al 2005). As of January 1 1995, the county had 416 184 inhabitants and 38 593 of them were born between January 1 1982 and December 31 1988.…”
Section: Study Area and Populationmentioning
confidence: 99%